Colloidal binary mixtures at fluid–fluid interfaces under steady shear: structural, dynamical and mechanical response. Issue 42 (8th September 2015) - Buttinoni, Ivo; Zell, Zachary A.; Squires, Todd M.; Isa, Lucio
Abstract : The mechanical properties of bidisperse colloidal monolayers under steady shear depend on the flowing modality of the individual particles, which is coupled to the monolayer structure. Abstract : We experimentally study the link between structure, dynamics and mechanical response of two-dimensional (2D) binary mixtures of colloidal microparticles spread at water/oil interfaces. The particles are driven into steady shear by a microdisk forced to rotate at a controlled angular velocity. The flow causes particles to layer into alternating concentric rings of small and big colloids. The formation of such layers is linked to the local, position-dependent shear rate, which triggers two distinct dynamical regimes: particles either move continuously ("Flowing") close to the microdisk, or exhibit intermittent "Hopping" between local energy minima farther away. The shear-rate-dependent surface viscosity of the monolayers can be extracted from a local interfacial stress balance, giving "macroscopic" flow curves whose behavior corresponds to the distinct microscopic regimes of particle motion. Hopping regions reveal a higher resistance to flow compared to the flowing regions, where spatial organization into layers reduces dissipation.